Effect of workload and job design on performance of health equipment management - Supangat, Ririn Widyowati; Ainun nisa, Farah Yasmine; Ernawaty, Ernawaty; Setyaningsih, Wahyu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Human Resources in the Medical Devices and Household Health Supplies Section feel the workload is uneven, job specifications overlap, and the high employee turnover has an impact on monitoring and data validation activities that have not been implemented in the management of medical equipment management. Researchers propose is a positive and significant effect of workload and job design on management performance. medical tools. This study aims to determine the effect of workload and work design on the performance of management of health equipment management in the section on Medical Devices and Household Health Supplies at the District X Health Office. Quantitative descriptive research with job analysis method and FTE workload analysis. Then proceed with analysis using SPSS.In the study, it was found that the workload of employees in the Medical Devices and Household Health Supplies sections was overloaded, namely 4.06, where four employees experienced overload and two employees experienced underload. So, it is necessary to realign the job description at the X District Health Office and the needs of employees, both government employees and Freelance employees. Workload has no effect on performance and job design has a significant effect on performance. It is useful to improve the performance of employees in the Medical Devices and household health supplies section by optimizing human resources by changing the composition of the number of workers and rearranging the Job Description in the section whose workload has been measured so that the workload is evenly distributed.Abstrak: Sumber Daya Manusia di Seksi Alat kesehatan dan Perbekalan Kesehatan Rumah Tangga merasakan beban kerja tidak merata, spesifikasi pekerjaan tumpang tindih serta tingginya turnover pegawai sehingga berimbas pada kegiatan Monitoring dan validasi data masih belum terlaksana dalam manajemen pengelolaan peralatan kesehatan.Penelitian ini bertujuan mengetahui pengaruh beban kerja dan desain pekerjaan terhadap kinerja manajemen pengelolaan peralatan kesehatan di seksi Alat kesehatan dan Perbekalan Kesehatan Rumah Tangga di Dinas Kesehatan Kabupaten X. Jenis penelitian deskriptif kuantitatif dengan metode analisa jabatan dan analisa beban kerja FTE. Kemudian dilanjutkan dengan analisis menggunakan SPSS dengan menggunakan uji validitas dan uji reliabilitas. Untuk analisis statistik, peneliti menggunakan uji tabulasi silang dan uji regresi logistik ganda.Dalam penelitian ditemukan bahwa beban kerja pegawai di seksi Alat kesehatan dan Perbekalan Kesehatan Rumah Tangga mengalami overload yaitu sebesar 4,06, dimana terdapat 4 orang pegawai yang mengalami overload dan 2 orang pegawai yang mengalami underload. Sehingga diperlukan penataan kembali job description di Dinas Kesehatan Kabupaten X dan kebutuhan pegawai baik itu pegawai negeri sipil maupun Tenaga Harian Lepas. Beban kerja tidak memiliki pengaruh terhadap kinerja serta desain pekerjaan memiliki pengaruh signifikan terhadap kinerja.Bermanfaat untuk meningkatkan kinerja pegawai pada Seksi Alat kesehatan dan perbekalan kesehatan rumah tangga dengan mengoptimalkan sumber daya manusia dengan mengubah komposisi jumlah pekerja dan menata kembali Deskripsi Pekerjaan pada bagian yang beban kerjanya sudah terukur sehingga beban kerja merata.